2020
DOI: 10.2147/clep.s242065
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluating the Effectiveness of an Additional Risk Minimization Measure to Reduce the Risk of Prescribing Mirabegron to Patients with Severe Uncontrolled Hypertension in Four European Countries</p>

Abstract: Background: Mirabegron, indicated for the treatment of overactive bladder, is contraindicated in patients with severe uncontrolled hypertension (systolic blood pressure ≥180 mm Hg and/or diastolic blood pressure ≥110 mm Hg). In September 2015, a Direct Healthcare Professional Communication (DHPC) letter was disseminated as an additional risk minimisation measure. Purpose: To assess the effectiveness of the DHPC in reducing the proportions of patients with severe or non-severe uncontrolled hypertension at mirab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Therefore, we did not conduct analyses to assess the effect of uncontrolled hypertension on the CV outcomes in this study. Furthermore, a European study that assessed the effectiveness of a direct healthcare communication letter to decrease the proportion of patients with uncontrolled hypertension prior to mirabegron initiation found that uncontrolled hypertension was uncommon before starting treatment with mirabegron even before the dissemination of the letter [ 39 ]. While it is possible that mirabegron might have influenced hypertension control in some patients, the previously mentioned results indicate that mirabegron initiation is quite rare in patients with uncontrolled hypertension, so there would be little to be learned from this type of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we did not conduct analyses to assess the effect of uncontrolled hypertension on the CV outcomes in this study. Furthermore, a European study that assessed the effectiveness of a direct healthcare communication letter to decrease the proportion of patients with uncontrolled hypertension prior to mirabegron initiation found that uncontrolled hypertension was uncommon before starting treatment with mirabegron even before the dissemination of the letter [ 39 ]. While it is possible that mirabegron might have influenced hypertension control in some patients, the previously mentioned results indicate that mirabegron initiation is quite rare in patients with uncontrolled hypertension, so there would be little to be learned from this type of analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have combined data from CPRD GOLD and CPRD Aurum without presenting direct comparisons between the databases, making it difficult to gauge the potential impact of heteregeneity. These include studies of incidence and prevalence study of rare conditions including juvenile idiopathic arthritis between 2000 and 2018,47 and neuromuscular conditions between 2000 and 201948; and a multicountry study examining the impact of a regulatory intervention to reduce inappropriate prescribing of mirabegron (a treatment for overactive bladder) to new users with severe or uncontrolled hypertension 49…”
Section: Discussionmentioning
confidence: 99%
“…These include studies of incidence and prevalence study of rare conditions including juvenile idiopathic arthritis between 2000 and 2018, 47 and neuromuscular conditions between 2000 and 2019 48 ; and a multicountry study examining the impact of a regulatory intervention to reduce inappropriate prescribing of mirabegron (a treatment for overactive bladder) to new users with severe or uncontrolled hypertension. 49 Other studies have used and compared data from CPRD GOLD and the QResearch database, which is also derived from EMIS primary care systems, and found baseline characteristics in patients with other conditions to be generally similar. [50][51][52][53][54] Strengths and limitations To our knowledge, this is the first published comparison of CPRD GOLD and CPRD Aurum to include both long-term incidence trends and detailed patient characteristics for specific conditions, and the first to include comparisons from a subset of overlapping practices in each database.…”
Section: Research In Contextmentioning
confidence: 99%